Attitudes of Saudis towards entertainment and its Correlation to social cohesion – A study applied to a sample of Saudi citizens in the city of Jeddah – - Algahtani, Eman Mubark (Journal of Humanities & Social Sciences, 2021)
The current study aimed at identifying the attitudes of Saudi society members towards the importance of practicing recreational activities for: the individual, the family and the society as well in relation to social cohesion. The current study, as one of the descriptive studies, is based on the social sample survey method. Based on the study methodology and the goals it seeks to achieve, the researcher relied on both the questionnaire and the observation as two main instruments for collecting the field study data. In the current study, the researcher relied on the purposive sample that is considered among the non-probability samples. It was applied to 415 members of the community in Jeddah including Saudi citizens of all educational, economic and age levels except for those under 16 years old. The study found out several results and the most prominent ones are: recreation achieves psychological balance for the individual and reduces life tensions and pressures. The practice of common entertainment among family members is a good opportunity to alleviate family disputes and tensions. It also supports the principles of cooperation, collective participation, and communication; accordingly, strengthening social relations reinforces the cohesion of the social structure. The results of the study revealed that recreation helps the individual to integrate into society which is useful for the renewal of the individual's activity. In addition, the collective practice of recreational activities strengthens the family relations. Recreation is an opportunity to form good relationships between society members. Finally, the study found out that families should be aware of the importance of practicing purposeful recreational activities starting from childhood to adulthood. That is to satisfy the psychological and social needs of its members.
Keywords: entertainment; attitude; social cohesion